Discretionary Accounting and Earnings Management Practices: Evidence from Sugar Industry of Pakistan - Yaseen, Hina Aziz; Ali, Moazzam; Ali, Moazzam; Nadeem, Tanzeela (Annals of Human and Social Sciences, 2025)
This study examines the accounting practices of earning management in the sugar industry of Pakistan. Using two broader categories; Accruals Based Earnings (AEM) and Real Earnings Management (REM), this study examines the phenomena of earning management. The study uses the data of 27 listed sugar firms on the Pakistan Stock Exchange for the period 2014-2023. The Modified Jones Model is applied to estimate the AEM and Roychowdhury Model is used for REM. The results of Pooled OLS suggest the complementary relationship between AEM and REM. Notably, AEM exhibits a stronger explanatory power in predicting REM, as reflected by its higher coefficient value. This study offers valuable insights for investors, regulators, and policymakers, particularly in the context of Pakistan’s sugar industry. The findings highlight the need for stricter and transparent financial reporting standards to enhance transparency and objectivity by implementing more rigorous regulations.